The Impact of Exchange Rate and Inflation on Composite Stock Price Index (IHSG) With Covid-19 As A Moderating Variable - Budiman, Arief; Murtadho, Muis (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
Covid-19 pandemic had posed serious threats to business sustainability in Indonesia. The purpose of this study is to find empirical evidence on the impact of foreign exchange rates and inflation against composite stock price index (IHSG), with Covid-19 as the moderating variables. As such, this study seeks to understand the impact of Covid-19, whether an increase or decrease in the composite stock price index. The quantitative study uses secondary data sources, i.e. Indonesian Stock exchange monthly publications and BNPB (National Disaster Management Coordinating Board /Badan Koordinasi Nasional Penanggulangan Bencana) between 2020 and 2022. The study found that foreign exchange rates had a direct impact during the pandemic period while inflation did not. The study also found that Covid-19 had a direct impact on the composite stock price index, foreign exchange and inflation, although the impact was relatively insignificant due to the short term nature of the variable.